Lack of a clinically important pharmacokinetic interaction between sofosbuvir or ledipasvir and hormonal oral contraceptives norgestimate/ethinyl estradiol in HCV‐Uninfected female subjects. (24th June 2014) - German, P.; Moorehead, L.; Pang, Phillip; Vimal, M.; Mathias, A.
Abstract This study evaluated the potential for a drug–drug interaction between HCV direct‐acting antivirals sofosbuvir or ledipasvir and oral hormonal contraceptive (OC) norgestimate/ethinyl estradiol (norgestimate 0.18/0.215/0.25 mg with ethinyl estradiol 25 μg). This was a 112‐day, open‐label, fixed‐sequence pharmacokinetic (PK) study in healthy female subjects that included a lead‐in cycle (OC only; N = 21), cycle 1 (OC only; N = 15), cycle 2 (OC + sofosbuvir; N = 15), and cycle 3 (OC + ledipasvir; N = 15). Administration of sofosbuvir with OC did not alter PK of norelgestromin (primary norgestimate metabolite) or ethinyl estradiol. Small increases in norgestrel (secondary norgestimate metabolite) AUCtau (19%) and Ctau (23%) with sofosbuvir were noted. Ledipasvir did not impact PK of norelgestromin or norgestrel but modestly increased ethinyl estradiol Cmax (40%). Sofosbuvir, GS‐ 331007 (predominant circulating metabolite of SOF), and ledipasvir PK were similar to historical data. Pharmacodynamic markers luteinizing hormone, follicle‐stimulating hormone, and progesterone values were generally comparable in all cycles. No loss in contraceptive efficacy is expected upon administration of sofosbuvir or ledipasvir/sofosbuvir with oral contraceptives containing norgestimate and ethinyl estradiol. The use of sofosbuvir or ledipasvir/sofosbuvir FDC with oral contraceptives is permitted.